Teaching Photochemical using Hydrillia Verticillata to Students with Intellectual Disabilities - Manullang, Tryastuti Irawati Belliny; Rakhmat, Cece; Haerudun, Dingding; Rochyadi, Endang; Nandyanto, Asep Bayu Dani; Muspita, Rila; Sumiroh, Evi (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study was to scrutinize how to teach photochemical using Hydrillia Verticillata for students with intellectual disabilities. The study used single-subject research towards six students with mild intellectual disability with IQ below 65 in one of the special schools in Bandung, Indonesia. The results of the study showed that students with mild intellectual disabilities with IQ less than 65 are able to learn the photochemical process through photosynthesis experimental demonstrations using Hydrillia Verticillata. Implementing the experimental demonstration through inquiry-based approach and pair work or group work, scaffolding the lesson, repeating the core questions are likely effective approaches and methods to teach students with intellectual disabilities to difficult concepts. Therefore, teaching challenging concepts to students with intellectual disabilities requires teachers to improve, develop and enhance their knowledge in order to help students to understand the concept.